2022
DOI: 10.1038/s41598-022-25054-z
|View full text |Cite
|
Sign up to set email alerts
|

Part three: a randomized study to assess biomarker changes in cigarette smokers switched to Vuse Solo or Abstinence

Abstract: Biomarkers of exposure (BoE) can help evaluate exposure to combustion-related, tobacco-specific toxicants after smokers switch from cigarettes to potentially less-harmful products like electronic nicotine delivery systems (ENDS). This paper reports data for one (Vuse Solo Original) of three products evaluated in a randomized, controlled, confinement study of BoE in smokers switched to ENDS. Subjects smoked their usual brand cigarette ad libitum for two days, then were randomized to one of three ENDS for a 7-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…The short-lived TXA 2 is metabolized to 2,3-d-TXB 2 and 11-dh-TXB 2 , which are routinely measured in urine as measures of platelet activation. The declines in 2,3-d-TXB 2 levels in 7 and 14 days are consistent with the findings from our previous work, which showed similar rapid declines following smoking abstinence or switching to ENDS products [ 21 , 22 ]. Several studies have reported that levels of 11-dh-TXB 2 are also higher in smokers compared to non-smokers (including moist snuff users) [ 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The short-lived TXA 2 is metabolized to 2,3-d-TXB 2 and 11-dh-TXB 2 , which are routinely measured in urine as measures of platelet activation. The declines in 2,3-d-TXB 2 levels in 7 and 14 days are consistent with the findings from our previous work, which showed similar rapid declines following smoking abstinence or switching to ENDS products [ 21 , 22 ]. Several studies have reported that levels of 11-dh-TXB 2 are also higher in smokers compared to non-smokers (including moist snuff users) [ 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…In an effort to identify BoPH that rapidly respond to smoking cessation and are mechanistically linked to the development of smoking-related diseases, RAI Services Company (RAIS) has identified two urinary eicosanoids, leukotriene E 4 (LTE 4 ) and 2,3-d-TXB 2 [ 14 ], and shown that the levels of eicosanoids rapidly decline upon smoking cessation or switching to non-combustible tobacco products [ 21 , 22 ]. With an objective to further qualify LTE 4 and 2,3-d-TXB 2 , we conducted a two-week biomarker study under clinical confinement, which we refer to as the Smoking Abstinence (SAB) study.…”
Section: Introductionmentioning
confidence: 99%
“…The significance threshold for secondary endpoints was 0.05. Forty (40) subjects were initially randomized in order to ensure that 30 subjects completed all test sessions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the companion PK study with similar product use parameters, two AEs (oropharyngeal pain and gastroesophageal reflux) were identified as related or possibly related to Vuse Solo use 39 . Furthermore, AEs related to Vuse Solo use in short-term switching studies have been reported and commonly include headache, nausea, and cough 38,40 . Reports of higher number of AEs during use of NRT gum relative to other products are not uncommon in studies with exclusive smokers, which may suggest that they are not familiar with sensations of oral product use 22 .…”
Section: Pk Parameter Amentioning
confidence: 99%
See 1 more Smart Citation